Neutrophil extracellular traps (NETs) are increased in rheumatoid arthritis-associated interstitial lung disease - Jing Xue; Miaomiao Nian; Yangyang Liang; Zeqin Zhu; Zhenyu Hu; Yuanyuan Jia; Shuhong Chi; Juan Chen (Respiratory Research)
Abstract Background Neutrophil extracellular trap (NET) formation has been implicated as a pathogenic mechanism in both rheumatoid arthritis (RA) and interstitial lung disease (ILD). However, the role of NETs in RA-associated ILD (RA-ILD) and the mechanisms driving NET formation remain unclear. This study aimed to assess the involvement of NETs in RA-ILD and elucidate the underlying mechanisms. Methods Single-cell sequencing was used to identify changes in the quantity and function of neutrophils in the lung tissue of a zymosan A (ZYM)-induced interstitial pneumonia arthritis model. Additionally, nuclear receptor 4A3 (NR4A3) interference was performed in HL-60 cells to assess its impact on NET formation and the transformation of MRC-5 cells into myofibroblasts. The clinical relevance of plasma myeloperoxidase-DNA (MPO-DNA), citrullinated histone 3 (Cit-H3), and cell-free DNA was evaluated in RA-ILD patients with different imaging types via a commercial enzyme-linked immunosorbent assay (ELISA). Results In the ZYM-treated SKG mouse model, which recapitulates key features of RA-ILD, an increased population of neutrophils in the lung tissue was primarily responsible for NET formation. Mechanistically, we found that interference with NR4A3 expression enhanced NET formation in HL-60 cells, which in turn promoted the differentiation of MRC-5 cells into myofibroblasts. Clinically, plasma MPO-DNA levels are elevated in patients with RA-nonspecific interstitial pneumonia (RA-NSIP), whereas Cit-H3 levels are elevated in RA-usual interstitial pneumonia (RA-UIP) patients compared with healthy subjects. ROC curve analysis further revealed that the combination of plasma MPO-DNA, rheumatoid factor (RF), and anti-citrullinated protein (anti-CCP) and the combination of Cit-H3, RF, and anti-CCP were superior diagnostic panels for NSIP and UIP in RA-ILD patients, respectively. Moreover, compared with those from healthy controls, neutrophils from patients with RA-UIP and RA-NSIP demonstrated a significantly increased ability to form NETs and induce the differentiation of MRC-5 cells into myofibroblasts. Specifically, RA-UIP patients exhibited a greater capacity for NET formation and the differentiation of MRC-5 cells into myofibroblasts than did RA-NSIP patients. Conclusions These findings suggest that targeting NETs may be a novel therapeutic approach for treating ILD in RA patients.